Risk factors for the development of diabetic nephropathy - Antić Miodrag; Jotić Aleksandra; Radović Milan; Seferović Jelena P.; Lalić Nebojša M.; Jovanović Dijana; Ležaić Višnja (Srpski Arhiv za Celokupno Lekarstvo, 2009)
Introduction. Results of epidemiological analysis show that one third of patients with diabetes mellitus develop diabetic nephropathy (DN). Strategies used until now to slow down the progression of DN were initiated when the symptoms of DN were already present. Objective. Our objective was to analyze the prevalence and characteristics of DN and to determine the factors leading to DN. Methods. Fifty-two patients with diabetes mellitus (DM) - 32 with type 1 aged 32 years and 20 with type 2 aged 59 years - were referred from the Institute of Endocrinology, Diabetes and Metabolic Diseases to the Department of Nephrology for kidney function evaluation. Apart from routine laboratory analyses, glomerular filtration rate was calculated using the MDRD formula (modification of diet in renal disease), the size of the kidney was measured by ultrasound, and kidney volume was calculated using the ellipsoid formula. Results Thirty percent of the patients revealed normal (eight patients with DM type 1) or satisfactory kidney function (eight patients with DM type 1) with physiological proteinuria. Micro-albuminuria (MAU) or pathological proteinuria (PRT) were found in 10 and 9 patients, respectively, with DM type 1, while decreased kidney function was found in one patient without proteinuria. MAU or PRT were found in four and eight patients, respectively, with DM type 2 and decreased kidney function in four patients without proteinuria. Kidney function was significantly lower in patients with DM type 2 in comparison to DM type 1, while the patients with decreased kidney function had a higher PRT. Compared to DM type 2, in DM type 1 patients, the kidney was longer, and parenchymal artery resistance index was lower in DM type 1 patients compared to DM type 2. Factors associated with DN were patient's age, duration of diabetes, systolic blood pressure, HbA1c and kidney volume. Conclusion. The prevalence of DN among the studied patients was 70%. Treatable factors associated with the development of DN are strict control of blood pressure and glycaemia control.